2011
DOI: 10.1371/journal.pone.0020656
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of the Honey Bee Microbiome Reveals Four Novel Viruses and Seasonal Prevalence of Known Viruses, Nosema, and Crithidia

Abstract: Honey bees (Apis mellifera) play a critical role in global food production as pollinators of numerous crops. Recently, honey bee populations in the United States, Canada, and Europe have suffered an unexplained increase in annual losses due to a phenomenon known as Colony Collapse Disorder (CCD). Epidemiological analysis of CCD is confounded by a relative dearth of bee pathogen field studies. To identify what constitutes an abnormal pathophysiological condition in a honey bee colony, it is critical to have cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
471
7
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(547 citation statements)
references
References 95 publications
31
471
7
8
Order By: Relevance
“…Notable viruses such as the Lake Sinai viruses (LSV 1 and 2) have been recorded in North America (Runckel et al . 2011) and Europe (Granberg et al . 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Notable viruses such as the Lake Sinai viruses (LSV 1 and 2) have been recorded in North America (Runckel et al . 2011) and Europe (Granberg et al . 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Library preparation was performed as described previously (37). Briefly, 4 μL of DNase-treated RNA was used for RT with the following conditions: 3Sol_N primer (final concentration, 8 μM) was mixed with RNA and denatured at 65°C for 5 min before incubation on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…LSV has only recently been described in adult honeybees (Runckel et al 2011) and was only found in three adult samples from Benin (Amakpe et al 2015). The transmission routes and associations of this virus with other pathogens or parasites are unknown (de Miranda et al 2013).…”
Section: Virusesmentioning
confidence: 99%